SMART-SPECIALIZATION AS A TOOL OF INNOVATIVE DEVELOPMENT OF THE REGIONAL ECONOMY (ON THE EXAMPLE OF ZAPOROIZHZHIA OBLAST) - Zavadskykh, Hanna; Tebenko, Vita (My University, 2022)
The European concept, which promotes economic growth through better disclosure of the potential of regions - SMART-specialization, is becoming more popular. In modern conditions, SMART-specialization has become a tool for finding and justifying the most competitive industries of a certain territory or country, the support of which can have a significant positive socio-economic effect. In recent years, EU countries have been actively using SMART specialization when developing regional development strategies. This experience is adopted by Ukraine, which is actively looking for potential industries and productions where the strategy of "smart specialization" or SMART-specialization can be implemented